Sulphate-reducing bacteria associated with biocorrosion: a review - Tania C. de Araujo-Jorge; Cláudia M. L. Melo Coutinho; Luiz Edmundo Vargas de Aguiar (Memorias do Instituto Oswaldo Cruz, 1992)
Biocorrosion means any process of corrosion in wich microorganisms are somehow involved. As far as the petroleum industry is concerned, the anaerobic type is the more important, with Sulphate-Reducing Bacteria (SRB) accouting for half of the described processes. SRB are obligate anaerobs that use sulphur, sulphate or other oxidized sulphur compounds as oxidizing agents when decomposing organic material. A typical product of SRB metabolism, hydrogen sulphide -H2S-, is extremely toxic. In the present work we review the literature on mechanisms underlying biocorrosive process in wich SRB are involved and summarize some of the ultrastructural and eletrochemical work developed using SRB obtained from water injection flow in wells located on PETROBRAS offshore marine plataforms, sampled directly in the field over metallic probes, or cultured under laboratory conditions. Biofilms develop when SRB adhere to inert surfaces. A high diversity of morphological types is found inside these biofilms. Their extracellular matrix is highly hydrated and mainly anionic, as shown by its avid reaction with cationic compounds like ruthenium red. We have noted that variations in iron contet lead to interesting changes in the ultrastructure of the bacterial cell coat and also in the rate of corrosion induced in metallic test cupons. Since routine methods to prevent and treat SRB contamination and biodeterioration involve the use of biocides that are toxic and always have some environmental impact, an accurate diagnosis of biocorrosion is always required prior to a treatment decision. We developed a method that detects and semi-quantifies the presence of living or dead SRB by using free silver potentials as an indicator of corrosive action by SRB-associated sulphides. We found a correlation between sulphide levels (determined either by spectrophotometry, or using a silver electrode -E(Ag)- that measured changes in free potentials induced by the presence of exogeneously added sulphide) and SRB concentration (enumerated by a culturing method). E (Ag) was characterized under a variety of conditions andwas found to be relatively immune to possible interference resulting from aeration of media or from the psence of iron corrosion products. The method offers a simple, rapid, and effective means of diagnosing biocorrosive processes prior to their control.